The Effectiveness of the Open University Digital Library in Fulfilling the Information Needs of Master of Management Students at UPBJJ-UT Jakarta - Pratiwi Anindita Adji (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Open University digital library plays an important role in supporting the learning process of open and distance education by providing various digital collections for all UT students. This research focuses on the effectiveness of UT's digital library in meeting the information needs of Master of Management students at UPBJJ-UT Jakarta. This research uses a quantitative approach with descriptive methods. The results in this study indicate that UT's digital library has not been fully effective in meeting the information needs of master of management students at UPBJJ-UT Jakarta. This is because UPBJJ-UT Jakarta master of management students are still experiencing several problems in utilizing the UT digital library, so the role of UT librarians is needed in promoting and socializing their digital library.